The Influence of Lemon Aromatherapy on Pain Reduction in Post-Caesarean Section Patients at PMI Hospital Bogor - Laelatus Siyam; Agus Purnama; Yeni Koto (UIMA Press, 2024)
Background: The issue of pain experienced by post-cesarean section mothers can be managed pharmacologically through pain relief medications or non-pharmacologically through the administration of lemon aromatherapy, which helps mothers feel more relaxed and calm. Objectives: This study aims to identify the influence of lemon aromatherapy on pain reduction in post-cesarean section patients. Methods: The research design used in this study is experimental research, specifically a quasi-experimental design with a Non-Equivalent Control Group or Non-Randomized Control Group Pretest-Posttest Design. The sample was selected using purposive sampling. To determine the minimum sample size for statistical testing, G Power was used, resulting in a total sample of 20 participants. The research instruments include a respondent identity questionnaire and an observation sheet questionnaire. Data analysis was conducted using the Wilcoxon-W test. Results: The results of the analysis using the Wilcoxon-W test showed a P-value of 0.388 > 0.05 with an effect size of -0.396. Conclusion: There is an influence before and after administering lemon aromatherapy in both the intervention and control groups, although the difference is not highly significant. However, the intervention group demonstrated a more dominant reduction in pain levels compared to the control group.